Word order in utterances of direct speech in English: a subtle balance between conventions and innovation - Grégoire LACAZE (E-REA)
Word order in an utterance produced by a speaker in connected speech is not supposed to be chaotic. Even though word order differs from one language to another, a given person who speaks his/her own mother tongue is normally able to say whether a given utterance is grammatical or not. This proficiency to point out what is correct and what is erroneous is a characteristic of an individual’s speaking his own language as a native speaker.The main focus of this paper is on how a producer of reported speech, namely a reporter, when led to build an occurrence of direct speech in English, will choose one word order for a sequence of words. In some cases, another word order would have given another fully grammatical utterance. What are the reasons behind a reporter favouring one particular word order? This analysis particularly tries to highlight what is at stake in this choice.